Projecting the chronic disease burden among the adult population in the United States using a multi-state population model - Ansah, John P.; Chiu, Chi-Tsun (Frontiers in Public Health, 2023)
Introduction: As the United States population ages, the adult population with chronic diseases is expected to increase. Exploring credible, evidence-based projections of the future burden of chronic diseases is fundamental to understanding the likely impact of established and emerging interventions on the incidence and prevalence of the chronic disease. Methods: We developed a multi-state population model that disaggregates the adult population in the United States into three health states, i.e., (a) healthy, (b) one chronic condition, and (c) multimorbidity. Data from the 1998 to 2018 Health and Retirement Study was used to estimate age, gender, and race-specific transition rates across the three health states, as input to the multi-state population model to project future chronic disease burden. Results: By 2050, 64.2% of individuals 50 years and older will have one or more chronic conditions. Most of the population 50 years and older with one or more chronic conditions are projected to be between the ages of 60 to 79 years, and the number of individuals 80 years and older with one or more chronic diseases is expected to more than double from 2020 to 2050. By race by 2050, 64.6% of non-Hispanic whites will likely have one or more chronic conditions, while for non-Hispanic black, 61.47%, Hispanic and other races 64.5%. Conclusion: The evidence-based projections provide the foundation for policymakers to explore the impact of interventions on targeted population groups and plan for the health workforce required to provide adequate care for current and future individuals with chronic diseases.